2013
DOI: 10.5194/acp-13-3909-2013
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in modelling heterogeneous chemistry and Arctic ozone depletion in the winter 2009/2010

Abstract: Stratospheric chemistry and denitrification are simulated for the Arctic winter 2009/2010 with the Lagrangian Chemistry and Transport Model ATLAS. A number of sensitivity runs is used to explore the impact of uncertainties in chlorine activation and denitrification on the model results. In particular, the efficiency of chlorine activation on different types of liquid aerosol versus activation on nitric acid trihydrate clouds is examined. Additionally, the impact of changes in reaction rate coefficients, in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 58 publications
8
81
0
Order By: Relevance
“…As commonly applied for simulating PSCs in atmospheric models (e.g. Wohltmann et al, 2013), NAT formation in EMAC is initiated at T NAT -3 K. This results in NAT clouds being formed before STS clouds, and thus NAT formation occurs at the expense of STS since the NAT clouds consume all the available HNO 3 . This therefore results in an overestimation of NAT since in reality STS and NAT clouds are often observed at the same time (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As commonly applied for simulating PSCs in atmospheric models (e.g. Wohltmann et al, 2013), NAT formation in EMAC is initiated at T NAT -3 K. This results in NAT clouds being formed before STS clouds, and thus NAT formation occurs at the expense of STS since the NAT clouds consume all the available HNO 3 . This therefore results in an overestimation of NAT since in reality STS and NAT clouds are often observed at the same time (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach is commonly applied for simulating PSCs in atmospheric models (e.g. Wohltmann et al, 2013). As was discussed by Wohltmann et al (2013), this approach technically results in NAT clouds being formed before STS clouds, and thus NAT formation occurs at the expense of STS since the NAT clouds consume all the available HNO 3 .…”
Section: Model-measurement Comparisonsmentioning
confidence: 99%
“…Although some recent studies have suggested that liquid PSCs play a dominant role in activating chlorine (e.g., Wegner et al, 2012;Wohltmann et al, 2013), the formation temperatures of solid nitric acid trihydrate (NAT, Hanson and Mauersberger, 1988) and ice particles remain convenient thresholds for the initiation of chlorine activation processes. In this study, we examine daily 12:00 UT minimum temperatures and calculations of area with temperatures below PSC thresholds (henceforth T min and A PSC , respectively).…”
Section: Temperature and Vortex Diagnosticsmentioning
confidence: 99%
“…The relative roles and temperature dependencies of surface reactions on and in water ice, nitric acid trihydrate ice, and supercooled liquid sulfuric acid−water−nitric acid and binary sulfuric acid−water particles at background levels have been research topics since the late 1980s, and some important questions have recently reemerged. Some recent studies have suggested that heterogeneous chemistry taking place on background particles of sulfuric acid and water is sufficient to explain nearly all of the chlorine activation (17)(18)(19) and ozone losses in both the Arctic and Antarctic (17) without any need for temperatures below −78°C or formation of polar stratospheric clouds, which would represent a major change in understanding. The potential for liquid binary aerosols to play some role in ozone loss under cold conditions was first identified decades ago (20,21).…”
Section: Lower Stratospheric Chemistrymentioning
confidence: 99%